Fenomena Authoritarian Leadership Post-Democracy di Indonesia: Kajian Atas Latar Belakang, Karakteristik dan Dampaknya - Nika Amalia Suhendro; Maulana Rifai; Indra Aditya (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the current era of democracy, every leader has his own character with a distinctive leadership style, as a country that adheres to a democratic system, the implementation of government administration is always required to comply with real democratic principles. But along the way, the development of democracy is colored by various systems that apply, one of which is guided democracy, a system that gives sovereignty to the people, but the decision is determined by the head of government or the president. This is in line with the concept put forward by Colin Crouch related to post-democracy that this condition is in line with the guided democracy system, namely the vagueness of public participation. This research uses qualitative methods and will provide a discussion of post-democracy in guided democracy.